1994
DOI: 10.1002/tea.3660310510
|View full text |Cite
|
Sign up to set email alerts
|

The Great evolution trial: Use of role‐play in the classroom

Abstract: This article gives both the pedagogic and scientific thinking that guided the construction of a classroom role‐play—The Great Evolution Debate. This role‐play is about the publication of Darwin's The Origin of Species, which is supposed to be on trial for blasphemy. Historical characters are used to show the range of ideas which were current at that time. The literature on learning history, and on learning about the nature of science, is discussed, leading to an examination of historical empathy as a classroom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0
3

Year Published

2003
2003
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(35 citation statements)
references
References 5 publications
0
32
0
3
Order By: Relevance
“…The potential benefits of role-playing have been reported for science education [2,3]. Duveen and Solomon reported that a role-playing exercise for the debate of evolution, especially related to Darwin's The Origin of Species, was considerably successful [4]. Among the categories of roleplaying reported by McSharry and Jones [1], many science teachers have explained metaphorical role-playing and analogy role-playing as fundamental "role-play" exercises.…”
Section: Introductionmentioning
confidence: 99%
“…The potential benefits of role-playing have been reported for science education [2,3]. Duveen and Solomon reported that a role-playing exercise for the debate of evolution, especially related to Darwin's The Origin of Species, was considerably successful [4]. Among the categories of roleplaying reported by McSharry and Jones [1], many science teachers have explained metaphorical role-playing and analogy role-playing as fundamental "role-play" exercises.…”
Section: Introductionmentioning
confidence: 99%
“…It is notable for the way it involves students in their own learning in a stimulating, 'reallife' environment. " Metode pembelajaran role playing sendiri telah di aplikasikan dalam berbagai displin ilmu, seperti drama, education, psychology (Britt, 1995), social sciences (Duveen and Solomon, 1994), philosophy, English literature (Wolf et al, 1994), foreign languages (Ladousse, 1987), environmental science, engineering, geography (Maddrell, 1994), health sciences, business (Brown, 1994;Egri, 1999), tourism and hospitality, ethics (Brown, 1994;Raisner, 1997), economics, marketing, political science and information technology (Kirkwood and Ross, 1997), dan designed computer software (Wagner, 1997).…”
Section: A Pendahuluanmentioning
confidence: 99%
“…Αθόκα ιηγόηεξεο έξεπλεο έρνπλ γίλεη ζην πιαίζην ηεο αμηνπνίεζεο ηεο ηζηνξίαο ησλ θπζηθώλ επηζηεκώλ κέζσ εθπαηδεπηηθνύ δξάκαηνο, αλ θαη ην έδαθνο είλαη γόληκν θαη θάπνηνη εξεπλεηέο έρνπλ ππνζηεξίμεη ην ζεκαληηθό ξόιν πνπ κπνξεί λα παίμεη ην εθπαηδεπηηθό δξάκα ζηελ θαιύηεξε θαηαλόεζε ηνπ πεξηερνκέλνπ ησλ θπζηθώλ επηζηεκώλ αιιά θαη ηεο θύζεο ηνπο (Bentley, 2000, Pantidos et al, 2001, Papadopoulos & Seroglou, 2005. Μηα πνιύ γλσζηή έξεπλα, ζην πεδίν απηό, είλαη ν ζρεδηαζκόο θη ε εθαξκνγή από ηνπο Duveen & Solomon (1994) παηρληδηνύ ξόισλ πνπ δηαπξαγκαηεύεηαη κηα θαληαζηηθή δίθε ηνπ Γαξβίλνπ κεηά ηε δεκνζίεπζε ηνπ έξγνπ ηνπ «Η θαηαγσγή ησλ εηδώλ». Σηηο ζπλεληεύμεηο πνπ πξαγκαηνπνηήζεθαλ κήλεο αξγόηεξα, ζην πιαίζην ηεο έξεπλαο απηήο, απνδείρζεθε όηη νη καζεηέο είραλ πνιύ ηζρπξέο αλακλήζεηο από ηε δξαζηεξηόηεηα εθείλε θαη ηα όζα είραλ κάζεη πξνεηνηκάδνληάο ηελ.…”
Section: τν εθπαηδεπηηθό δξάκα ζηε δηδαθηηθή ησλ θπζηθώλ επηζηεκώλunclassified